THE IMPLEMENTATION OF CONTEXTUAL TEACHING AND LEARNINGMETHOD TO INCREASE STUDENTS’ VOCABULARY MASTERY OF THE SEVENTH GRADE AT MTs NEGERI 02. TOLITOLI - Hidayati Hidayati (Universitas Madako Tolitoli, 2018)
The objective of this research is to find out whether the using of contextual teaching and learning can increase students’ vocabulary mastery. It is a pre-experimental research. The study was taken by the seventh grade of MTs Negeri 02. Tolitoli. It was conducted in one class (VII D). The data were obtained through a pre-test and post-test.The mean score of pre-test was (65.6) while in the post-test improved up to (74.07). Moreover the Minimum Mastery Criterion of English lesson was 75 (seventy-five). Then the data of both test were analyzed by using T-test, and the result showed that the T-count value was 5.48 greater than T-table value was 1.701 It can be inferred that the using of contextual teaching and learning method can increase students’ vocabulary mastery. Keywords: Increase, Vocabulary, Contextual Teaching Learning.